Congenital Hypothyroidism Long‐Term Follow‐up Project: Navigating the Rough Waters of a Multi‐Center, Multi‐State Public Health Project. Issue 3 (18th November 2014) - Wintergerst, Kupper; Gembel, Gina; Kreipe, Tracey; Zeller, Patrick; Eugster, Erica; Young, Bill; Andruszewski, Karen; Kleyn, Mary; Cunningham, Troi; Fawbush, Sandy; Vanderburg, Nancy; Sockalosky, Joe; et al.
Abstract: The Region 4 Midwest Genetics Collaborative, made up of seven regional states (Illinois, Indiana, Kentucky, Michigan, Minnesota, Ohio, and Wisconsin), brought together pediatric endocrinologists, state laboratory experts, public health follow‐up specialists, and parents of children with congenital hypothyroidism (CH) to identify the three‐year follow‐up management and education patterns of primary care clinicians and pediatric endocrinologists in the care of children diagnosed with CH by state newborn screening (NBS) programs. Among a number of challenges, each state had different NBS methods, data systems, public health laws, and institutional review board (IRB) requirements. Furthermore, the diagnosis of CH was complicated by the timing of the NBS sample, the gestational age, weight, and co‐morbidities at delivery. There were 409 children with CH identified through NBS in 2007 in the seven state region. The clinician of record and the parents of these children were invited to participate in a voluntary survey. Approximately 64 % of clinician surveys were collected with responses to questions relating to treatment, monitoring practices, educational resources, genetic counseling, and services provided to children with confirmed CH and their families. Nearly one‐quarter (24 %) of parents surveyed responded to questions relating to treatment, education, genetic counseling, resources, and services they received or would like to receive. De‐identified data from six of the seven states were compiled for analysis, with one state being unable to obtain IRB approval within the study timeline. The data from this collaborative effort will improve state follow‐up programs and aid in developing three‐year follow‐up guidelines for children diagnosed with CH. To aid in the facilitation of similar public health studies, this manuscript highlights the challenges faced, and focuses on the pathway to a successful multi‐state public health endeavor.